General Image Of Abdurahman Jami In Literary And Historical Sources Of The Xv-Xvi Century - Rajabova Burobiya Tangirovna (Emerging Frontiers Library for The American Journal of Social Science and Education Innovations, 2025)
The article examines about 20 historical and literary sources with information about Abdurrahman Jami, as well as some of the works of the great thinker. In a certain sense, the issue and problem of “Jomi and Uzbek literature” has been revealed. In the studied books, Jami is mentioned not only as a brilliant poet and writer, but also as a literary critic, philosopher, lawyer, sufi, and public figure. The works of poets and writers who came to fiction under the influence of the Navai and Jami schools were examined, and the issue of tradition and literary influence was also highlighted.